2013
DOI: 10.4021/ijcp79w
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pulmonary Hypertension of the Newborn: Recent Advances in the Management

Abstract: Persistent pulmonary hypertension of the newborn (PPHN) is a medical emergency in the neonatal period, which occurs due to failure of normal postnatal transition of fetal circulation. Despite availability of numerous treatment modalities, associated mortality and morbidity remain high. Therefore, awareness of predisposing conditions, and early diagnosis and management may help improving outcome in PPHN. To provide an overview of anatomic and functional anomalies of PPHN, and available treatment options with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…[2] PPHN is associated with a high mortality rate, especially in resource-limited settings. [4] Of the 72 neonates included in this study, 25 (34.7%) did not survive. Similar mortality rates, either directly or indirectly related to PPHN, were reported in previous studies across the world, e.g.…”
Section: Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…[2] PPHN is associated with a high mortality rate, especially in resource-limited settings. [4] Of the 72 neonates included in this study, 25 (34.7%) did not survive. Similar mortality rates, either directly or indirectly related to PPHN, were reported in previous studies across the world, e.g.…”
Section: Researchmentioning
confidence: 91%
“…[2,3] Despite the progress in treating PPHN, it remains a potentially fatal disease, especially in resource-limited settings. [4] The reported overall mortality ranges from 4% to 33% in developed countries [2] and from 25% to 48% in developing countries. [5,6] In South Africa (SA), previous studies reported the incidence of PPHN to be 1.1%, with a mortality rate of 31% at Tygerberg Children's Hospital [7] and 48% at Chris Hani Baragwanath Academic Hospital.…”
Section: Researchmentioning
confidence: 99%
“…The management of PPHN is widely varied with the ideal combination and doses of therapeutic agents unknown [11]. The results from the preliminary study looking at variance among disciplines in the preparation and management of a critically ill infant with PPHN show a trend toward alignment of attendings and NNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnosis of pulmonary hypertension was based on persistent hypoxemia despite ventilation with 100% oxygen, and a difference in oxygen saturation between the upper and lower limbs of ≥ 10% [8], which is usually seen in highrisk term or late preterm infants [9]. Echocardiography criteria for diagnosis of PPHN were based on both qualitative and Neonatal Pulmonary Hypertension Int J Clin Pediatr.…”
Section: Methodsmentioning
confidence: 99%